Perpendicular Current Reduction Caused by Cold Ions of Ionospheric Origin in Magnetic Reconnection at the Magnetopause: Particle‐in‐Cell Simulations and Spacecraft Observations. Issue 19 (1st October 2018) - Toledo‐Redondo, Sergio; Dargent, Jérémy; Aunai, Nicolas; Lavraud, Benoit; André, Mats; Li, Wenya; Giles, Barbara; Lindqvist, Per‐Arne; Ergun, Robert E.; Russell, Christopher T.; Burch, James L.
Abstract: Cold ions of ionospheric origin are present throughout the Earth's magnetosphere, including the dayside magnetopause, where they modify the properties of magnetic reconnection, a major coupling mechanism at work between the magnetosheath and the magnetosphere. We present Magnetospheric MultiScale (MMS) spacecraft observations of the reconnecting magnetopause with different amounts of cold ions and show that their presence reduces the Hall term in the Ohm's law. Then, we compare two particle‐in‐cell simulations, with and without cold ions on the magnetospheric side. The cold ions remain magnetized inside the magnetospheric separatrix region, leading to the reduction of the perpendicular currents associated with the Hall effect. Moreover, this reduction is proportional to the relative number density of cold ions. And finally, the Hall electric field peak is reduced along the magnetospheric separatrix owing to cold ions. This should have an effect on energy conversion by reconnection from electromagnetic fields to kinetic energy of the particles. Plain Language Summary: The magnetic field of Earth creates a natural boundary that isolates and protects us from the particles and fields coming from the Sun, typically known as the solar wind. This natural shield is called the magnetosphere and is filled by plasma. The particles are coming from the solar wind and are usually deviated around the magnetosphere. However, various mechanisms are capable of interconnecting these two regions of plasma, permitting the exchange of mass and energy. Magnetic reconnection is a primary coupling mechanism and the driver of storms and substorms inside the magnetosphere. In this work, we investigate what occurs when particles of very low energy (cold ions) of ionospheric origin reach the reconnecting boundary between the solar wind and the magnetosphere. We use both spacecraft observations and numerical simulations, and we find that they modify the way reconnection operates, by reducing the currents carried by electrons. The electric fields associated with energization of particles are reduced as well under the presence of cold ions coming from the ionosphere. Key Points: We compare full particle‐in‐cell simulations and MMS observations of magnetic reconnection with cold ions The perpendicular current reduction is linearly proportional to the cold ion density ratio inside the separatrix region The Hall electric field peak is reduced along the separatrix when cold ions are present